Empowerment of Youth Organizations in Processing Plastic Waste With a Waste Bank System in RW 05 Cigoong Sub-Village. - Muhammad Thoriqo Haqqi; Muhammad Al Mighwar; Nurazki Aslamiah; Delia Febyarinzani Alami (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
This study aims to explore the empowerment of Karang Taruna RW 05 Cigoong Mekarsari Pangalengan Village in managing plastic waste using a waste bank system. Participatory research methods were used in this study to analyze the implementation of this system and to identify supporting factors and obstacles. The active participative role of the community is needed to run this waste bank system. So that the waste bank program has clear continuity in its journey and can provide benefits that can be felt by the private sector and society.